2022
DOI: 10.3389/fmicb.2022.836076
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lineage of Cile-Like Viruses Discloses the Phylogenetic Continuum Across the Family Kitaviridae

Abstract: An increasing number of plant species have been recognized or considered likely reservoirs of viruses transmitted by Brevipalpus mites. A tiny fraction of these viruses, primarily those causing severe economic burden to prominent crops, have been fully characterized. In this study, based on high-throughput sequencing, transmission electron microscopy analyses of virions in plant-infected tissues, viral transmission experiments, and the morphoanatomical identification of the involved Brevipalpus mites, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 56 publications
0
16
0
2
Order By: Relevance
“…1a). Phylogenetic analysis based on amino acid sequences of RdRp showed that RdFV clustered with plant-infecting furoviruses in Virgaviridae family, which contained plant virgavirus lineages and unclassified insect-infecting virga-like virus group, such as Hubei virga-like viruses [38][39][40] (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). Phylogenetic analysis based on amino acid sequences of RdRp showed that RdFV clustered with plant-infecting furoviruses in Virgaviridae family, which contained plant virgavirus lineages and unclassified insect-infecting virga-like virus group, such as Hubei virga-like viruses [38][39][40] (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis showed that the insect-specific RdFV, gramineous plants-infecting furovirues, and insect-specific Hubei virgalike viruses belong to Virgaviridae family [38][39][40] . The close phylogenetic relationship between insect-infecting virgaviruses and their plantinfecting counterparts suggests that they might share the common virus origin(s) 39,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both CiLV-C2 and CiLV-C2H encodes a 7-kDa transmembrane protein (p7) ( Roy et al., 2013b ; Melzer et al., 2013 ) but the ORF p7 is absent in the CiLV-C2H2 genome as the similar genome structure was observed in the RNA2 genome segment of CiLV-C ( Locali-Fabris et al., 2006 ). The RNA2 genome sequences between ORF1 (p15) and ORF2 (p61) [with or without p7 ORF] are the most variable region among cileviruses ( Ramos-González et al., 2022 ). Current demarcation criteria for species of the genus Cilevirus are based on <85% aa sequence identity for the proteome but there is no cut off value was determined for cilevirus strain identification.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission assays also proved that B. papayensis , B. obovatus, and B. yothersi are, at least under our experimental conditions, unable to transmit CiBSV isolates. It should be noted that these experiments were carried out in conditions equivalent to those commonly described for the transmission of other Brevipalpus -transmitted viruses [ 7 , 29 ]. Further studies could be performed using citrus seedlings as test plants to assess the transmission efficiency of CiBSV by B. azores .…”
Section: Discussionmentioning
confidence: 99%